If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Z + -10 = -18 Reorder the terms: -10 + Z = -18 Solving -10 + Z = -18 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + Z = -18 + 10 Combine like terms: -10 + 10 = 0 0 + Z = -18 + 10 Z = -18 + 10 Combine like terms: -18 + 10 = -8 Z = -8 Simplifying Z = -8
| 12-2x6+2/2=X | | 2+5-3*4/2 | | 2k+3=-17 | | p-25=15/4(h-18) | | -2(w-5)=-4w+26 | | 4y-3+y+20=6y+20-4y | | -20+4P=0 | | p-25=15/4(h-4-18) | | a=b+3c | | -x^2-7x-6=0 | | p-25=18(h-4) | | (2x)(2x)=2 | | 60x-0.2x^2=0 | | 3a-10=x | | (3c/2b^4c^2)(4b/9c) | | x+5=y-15 | | 10-3a=x | | 4x^2-6=5u | | p-22=18(h-6) | | a^2-3a-2=2 | | ln(x+3)+2=8 | | p-18=9(h-6) | | 2(-23/2)=x | | 2(-3/2)=x | | 7x+10y=43.70 | | 8-5X=1-X | | 2x^3+7x^2+6x=0 | | p-22=63/2(h-6) | | 11Z+20=0 | | y=(2x-5)(2x-3) | | 24x+12(-79/78)=-11 | | S=5*4+8*5+8*4+8*3 |